Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

$$ \int_2^4\frac{\sqrt{\log(9-x)}}{\sqrt{\log(9-x)}+\sqrt{\log(3+x)}}dx=1$$

share|cite|improve this question
In general: $\int_2^4 \frac{f(x)}{f(x)+f(6-x)}\,dx=1$. – pharmine Nov 10 '11 at 5:22
why is this the case? – vivaelche05 Nov 10 '11 at 5:26
I posted an answer below. – pharmine Nov 10 '11 at 5:50
up vote 7 down vote accepted

We show that $I=\int_2^4 \frac{f(x)}{f(x)+f(6-x)}\,dx$ equals $1$, where $f(x)=\sqrt{\log(9-x)}$.

Proof. By making a substitution $y=6-x$, we get $$I=\int_4^2 -\frac{f(6-y)}{f(y)+f(6-y)}\,dy=\int_2^4 \frac{f(6-y)}{f(y)+f(6-y)}\,dy.$$

Therefore $$\begin{align*}2I&=\int_2^4 \frac{f(x)}{f(x)+f(6-x)}dx+\int_2^4 \frac{f(6-y)}{f(y)+f(6-y)}dy\\ &=\int_2^4 \frac{f(x)}{f(x)+f(6-x)}dx+\int_2^4 \frac{f(6-x)}{f(x)+f(6-x)}dx=\int_2^4 1\,dx =2.\end{align*}$$

Edit. In the last part, $y$ is a dummy variable and can be changed to $x$ or any other variable you like.

Edit2. If you don't like the same $x$ being used, you could use another variable, say $s$, so that with two substitutions $$\begin{align*}2I&=\int_2^4 \frac{f(x)}{f(x)+f(6-x)}dx+\int_2^4 \frac{f(6-y)}{f(y)+f(6-y)}dy\\ &=\int_2^4 \frac{f(s)}{f(s)+f(6-s)}ds+\int_2^4 \frac{f(6-s)}{f(s)+f(6-s)}ds=\int_2^4 1\,ds =2.\end{align*}$$

share|cite|improve this answer
how did f(6-y) become f(6-x) in the numerator of the second integrand on the last line? – vivaelche05 Nov 10 '11 at 5:50
Because $y$ is a dummy variable; please see my edited comment. – pharmine Nov 10 '11 at 5:53
Wow, thank you. can I ask, conceptually, why this is true for all integrable f(x)'s? – vivaelche05 Nov 10 '11 at 15:18
As Dinesh points out, $g(x)=\frac{f(x)}{f(x)+f(6-x)}$ satisfies $g(x)+g(6-x)=1$ (more generally, $g(x)+g(a-x)=b$ where $a$ and $b$ are constants); this is the condition where you can use this integration trick. – pharmine Nov 10 '11 at 15:33

$ \int^a_b f(x)\,dx $ = $ \int^a_b f(a+b-x)\,dx $ We can prove this by changing the dummy variable x to a+b-x, we get the integrand as $-f(a+b-x)\,dx$ and by changing the limits accordingly with $a+b-b$ and $a+b-a$, i.e. Now the integral becomes $-\int^b_af(a+b-x)dx$=$ \int^a_b f(a+b-x)dx $

The function given in the question satisfies the property that $f(x)+f(6-x)=1$. Let the integral be $I$ then $2I= \int^a_b f(x)\,dx+ \int^a_b f(a+b-x)dx=\int^a_b f(x)+f(a+b-x)\,dx=\int^a_b\,dx=a-b$, In your case $a-b=2$, hence $2I=2$. So $I=1$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.